Temporal trends of survival and utilization of mechanical circulatory support devices in patients with in‐hospital cardiac arrest secondary to ventricular tachycardia/ventricular fibrillation. Issue 4 (21st February 2019) - Patel, Nileshkumar J.; Atti, Varunsiri; Kumar, Varun; Panakos, Andrew; Anantha Narayanan, Mahesh; Bhardwaj, Bhaskar; Arora, Shilpkumar; Deshmukh, Abhishek J; Patel, Nish; Basir, Mir B.; Cohen, Mauricio G.; Kini, Annapoorna S.; et al.
Abstract: Background: Pulseless ventricular tachycardia/ventricular fibrillation (VT/VF) is the initial rhythm in a third of in‐hospital cardiac arrest patients. Mechanical circulatory support (MCS) device use remains poorly understood in this population. Methods: We conducted an observational analysis of temporal trends in the utilization of MCS in VT/VF IHCA between January 2008 and December 2014 utilizing the Nationwide Inpatient Sample (NIS) database. Using multivariable analysis, we assessed factors associated with MCS use and survival to discharge. Results: Among 151, 628 hospitalizations with VT/VF IHCA, 14, 981 (9.9%) received MCS. Intra‐aortic balloon pump (IABP) was the most commonly used MCS (9.1%). From 2008 to 2014, there was significant increase in the utilization of MCS (8.7–11%; p trend < 0.0001). On multivariable analysis, there was 12‐fold increase and three‐fold increase in the utilization of PVAD and ECMO respectively; however, there was no significant change in the use of IABP. Over the seven‐year sample period, there was significant increase in the overall survival to hospital discharge (35.4–43.5%; p trend < 0.0001). Survival to hospital discharge increased in both MCS and non‐MCS groups. Conclusion: There was significant increase in utilization of MCS after VT/VF IHCA during the study period. IABP was the most commonly utilized MCS. The survival to hospital discharge increased in the overall study population including both MCS and non‐MCS groups. Future studies are needed to identify patient population most likely to benefit from the use of MCS after VT/VF IHCA.